2018
DOI: 10.1038/s41598-018-20903-2
|View full text |Cite
|
Sign up to set email alerts
|

Large uniaxial magnetostriction with sign inversion at the first order phase transition in the nanolaminated Mn2GaC MAX phase

Abstract: In 2013, a new class of inherently nanolaminated magnetic materials, the so called magnetic MAX phases, was discovered. Following predictive material stability calculations, the hexagonal Mn 2 GaC compound was synthesized as hetero-epitaxial films containing Mn as the exclusive M-element. Recent theoretical and experimental studies suggested a high magnetic ordering temperature and non-collinear antiferromagnetic (AFM) spin states as a result of competitive ferromagnetic and antiferromagnetic exchange interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 32 publications
4
49
0
Order By: Relevance
“…This is indicative of a parameter forcing the magnetic moment to be localized, raising a question of the proper value of U eff to describe Mn 2 GaC in particular and magnetic MAX phases in general. These results indicate the PBE or PBE + U (with U eff ≤ 0.25 eV) is the most appropriate functionals to use until proven otherwise for describing Mn 2 GaC when compared to experimental results [26][27][28][29] .…”
Section: Resultsmentioning
confidence: 90%
See 3 more Smart Citations
“…This is indicative of a parameter forcing the magnetic moment to be localized, raising a question of the proper value of U eff to describe Mn 2 GaC in particular and magnetic MAX phases in general. These results indicate the PBE or PBE + U (with U eff ≤ 0.25 eV) is the most appropriate functionals to use until proven otherwise for describing Mn 2 GaC when compared to experimental results [26][27][28][29] .…”
Section: Resultsmentioning
confidence: 90%
“…The first experimental evidence of magnetic MAX phases were quaternary Mn-doped Cr 2 GeC 10 12 , Cr 2 GaC 13 – 17 and Cr 2 AlC 14 , 18 , 19 followed by (Mo,Mn) 2 GaC 20 , 21 and (V,Mn) 3 GaC 2 22 . Examples of ternary MAX phases with demonstrated magnetic properties are Cr 2 AlC 23 , 24 , Cr 2 GeC 11 , 24 , Cr 2 GaC 13 , 25 , Cr 2 GaN 25 , and Mn 2 GaC 26 29 . The Cr-based phases have all been made in bulk form and as thin films, whereas Mn 2 GaC have been synthesized in thin film form only.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[12][13][14]. Recent studies revealed a high magnetic ordering temperature (above 200 K) which is strongly influenced by the Mn concentration at the M-site and by the choice of the A-element [15][16][17][18][19][20][21][22]. The highest phase purity and structural quality has been achieved in (Cr 0.5 Mn 0.5 ) 2 GaC films epitaxially grown on MgO (111) substrates [23].…”
Section: Introductionmentioning
confidence: 99%